Contribución al estudio de los ascomicetes españoles : I. Algunas especies nuevas o raras encontradas en Cataluña y Madrid - Calonge, Francisco de Diego; Rocabruna i Llavanera, August; Tabarés Carriedo, Manuel; Rodríguez, N. B. (Revista Catalana de Micologia, 2007)
18 species of Ascomycetes are described, two of them, Aleuria rhenana Fuckel, and Fimaria ripensis (E.C. Hansen) Korf are new to the Spanish Catalogne, and three are mentioned for the second instance in Spain: Gyromitra wamei(Peck) Harmaja, Geopyxis majalis (Fr.) Sacc., and Peziza endocarpoides Berk. Notes on the geographical distribution of the other species are also given.